A Novel Bimodal Imaging Agent Targeting HER2 Molecule of Breast Cancer - Wei Lv; Yamei Shen; Hengli Yang; Rui Yang; Wenbin Cai; Jian Zhang; Lijun Yuan; Yunyou Duan; Li Zhang (Journal of Immunology Research)
Nanobubble (NB), a newly developed nanoscaled ultrasound contrast agent (UCA) for molecular imaging, has been widely researched for these years. Targeting it with functional molecule, nanobubble can adhere selectively to cellular epitopes and receptors outside the vasculature via enhanced permeability and retention (EPR) effect of tumor blood vessel. To enhance the targeting rate of our previous prepared NBs-Affibody for HER2 (+) breast cancer imaging, we introduced a near-infrared fluorescent (NIRF) dye, IR783, in this study to enhance tumor-specific targeting rate and provide a promising modality for dual-mode imaging. The prepared IR783-NBs-Affibody presented a uniform nanoscale size around 482.7 ± 54.3 nm, good biosecurity, and stability over time. The encapsulation efficiency (EE) of IR-783 was 15.09% in the conjugates leading to a successful NIR fluorescence and ultrasound enhancement imaging ex vivo. IR783-NBs-Affibody was able to automatically accumulate on BT474 cells with a highly increased targeting rate of 85.4% compared with previous NBs-Affibody of 26.6%, while Affibody-guided HER2 binding was only found in HER2-positive cell lines (BT474 and T-47D). The newly developed IR783-NBs-Affibody is characterized with favorable HER2 targeting ability and bimodal imaging capability for breast cancer. Thus, IR783-NBs-Affibody holds great potential in molecular diagnosis for patients with breast cancer.